Evaluation of superparamagnetic iron oxide nanoparticles (Endorem®) as a photoacoustic contrast agent for intra‐operative nodal staging. (29th October 2012) - Grootendorst, Diederik J.; Jose, Jithin; Fratila, Raluca M.; Visscher, Martijn; Velders, Aldrik H.; Ten Haken, Bennie; Van Leeuwen, Ton G.; Steenbergen, Wiendelt; Manohar, Srirang; Ruers, Theo J. M.
<x xml:space="preserve">Abstract</x> Detection of tumor metastases in the lymphatic system is essential for accurate staging of malignancies. Commercially available superparagmagnetic nanoparticles (SPIOs) accumulate in normal lymph tissue after injection at a tumor site, whereas less or no accumulation takes place in metastatic nodes, thus enabling lymphatic staging using MRI. We verify for the first time the potential of SPIOs, such as Endorem® as a novel photoacoustic (PA) contrast agent in biological tissue. We injected five Wistar rats subcutaneously with variable amounts of Endorem® and scanned the resected lymph nodes using a tomographic PA setup. Findings were compared using histology, vibrating sample magnetometry (VSM) and 14 T MR‐imaging. Our PA setup was able to detect the iron oxide accumulations in all the nodes containing the nanoparticles. The distribution inside the nodes corresponded with both MRI and histological findings. VSM revealed that iron quantities inside the nodes varied between 51 ± 4 and 11 ± 1 µg. Nodes without SPIO enhancement did not show up in any of the PA scans. Iron oxide nanoparticles (Endorem®) can be used as a PA contrast agent for lymph node analysis and a distinction can be made between nodes with and nodes without the agent. This opens up possibilities for intra‐operative nodal staging for patients undergoing nodal resections for metastatic malignancies. Copyright © 2012 John Wiley & Sons, Ltd.